Advertisements
Advertisements
Question
`d/(dx)[sin^-1(xsqrt(1 - x) - sqrt(x)sqrt(1 - x^2))]` is equal to
Options
`1/(2sqrt(x(1 - x))) - 1/sqrt(1 - x^2)`
`1/sqrt(1 - {xsqrt(1 - x) - sqrt(x(1 - x^2))}^2`
`1/sqrt(1 - x^2) - 1/(2sqrt(x(1 - x))`
`1/sqrt(x(1 - x)(1 - x)^2`
MCQ
Solution
`1/sqrt(1 - x^2) - 1/(2sqrt(x(1 - x))`
Explanation:
Let y = `d/(dx)[sin^-1(xsqrt(1 - x) - sqrt(x) sqrt(1 - x^2))]`
Put x = sin α and `sqrt(x)` = sin β
∴ `y = d/(dx)[sin^-1(sinalpha sqrt(1 - sin^2 beta) - sin beta sqrt(1 - sin^2 alpha))]`
= `d/(dx) [sin^-1 (sin alpha - beta)] = d/(dx) (alpha - beta)`
= `d/(dx) [sin^-1x - sin^-1 sqrt(x)]`
= `1/sqrt(1 - x^2) - 1/(2sqrt(x)sqrt(1 - x))`
= `1/sqrt(1 - x^2) - 1/(2sqrt(x(1 - x))`
shaalaa.com
Is there an error in this question or solution?